Embracing Jesus: Mystical Union with Christ in Seventeenth-century Art and Imagination - Buettner, Jamie (The international journal of religion and spirituality in society, 2014)
Emphasis on personal spirituality in the wake of the Protestant Reformation and Catholic Counter-Reformation had enormous impact on religious art. To give visual expression to this new tenor of feminine religious interiority, European artists drew upon a long tradition of nuptial imagery, utilizing the "bride of Christ" metaphor. Catholic religious women experienced mystical marriages with Jesus, pictorially depicted through corporeal and highly gendered gestures. Mystical union with Christ represented the highest ascent toward God and epitomized the Counter-Reformation female religious experience. Despite reformers’ restrictions on imagery, mystical union was also visually represented in sacred emblem books for use in Protestant devotion. Visual allegories of the biblical Song of Songs provided the source for illustrations that depicted mystical union in scenes of tenderness between the female "Soul" and "Divine Love." This article traces the influences of art historical precedent on the phenomenon of early modern imagery of mystical union, as well as ties historical evidence of female agency with the use of this imagery in private devotion. Identification as a "bride of Christ" provided a liberating possibility that enabled seventeenth-century women to cope with or circumvent their constricting material existences.